RETRACTED: Effect of intranasal oxytocin administration on psychiatric symptoms: A meta-analysis of placebo-controlled studies. Issue 3 (30th August 2015) - Hofmann, Stefan G.; Fang, Angela; Brager, Daniel N.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the authors and Editor-in-Chief of the journal. It was brought to the authors' attention that there were several significant data analytic errors linked to the data entry and the software program that was used in the published meta-analysis comparing the effect of intranasal oxytocin versus placebo administration on psychiatric symptoms. Correcting these errors changed the main result of this study. The authors greatly apologize to the journal, the reviewers, and readers for the errors in the original article, and would like to thank the readers who brought the errors to their attention.